2009
DOI: 10.1194/jlr.p800025-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Partial recovery of the endothelial glycocalyx upon rosuvastatin therapy in patients with heterozygous familial hypercholesterolemia

Abstract: The endothelial glycocalyx has been shown to serve as a protective barrier between the flowing blood and the vessel wall in experimental models. The aim of this study was to evaluate whether hypercholesterolemia is associated with glycocalyx perturbation in humans, and if so, whether statin treatment can restore this. We measured systemic glycocalyx volume (V G ) in 13 patients with heterozygous familial hypercholesterolemia (FH) after cessation of lipid-lowering therapy for a minimum of 4 weeks and 8 weeks af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 29 publications
(38 reference statements)
2
53
0
3
Order By: Relevance
“…Consistent with this theory, flow-mediated dilatation is impaired is impaired in patients with coronary disease [8]. There is thinning of the glycocalyx in diabetes [2] and heterozygous familial hypercholesterolemia [9], both diseases characterised by proneness to coronary disease. Constantinescu et al [10] demonstrated thinning of the glycocalyx by oxidised LDL.…”
Section: The Importance Of Flow Mediated Arterial Dilatation (Fmd)supporting
confidence: 62%
“…Consistent with this theory, flow-mediated dilatation is impaired is impaired in patients with coronary disease [8]. There is thinning of the glycocalyx in diabetes [2] and heterozygous familial hypercholesterolemia [9], both diseases characterised by proneness to coronary disease. Constantinescu et al [10] demonstrated thinning of the glycocalyx by oxidised LDL.…”
Section: The Importance Of Flow Mediated Arterial Dilatation (Fmd)supporting
confidence: 62%
“…[33][34][35] Mean systemic ESL volume in healthy individuals was shown to be 1.5-1.7 L, whereas much lower systemic ESL volumes were found in treated (1.1 L) and untreated (0.8 L) patients with heterozygous familial hypercholesterolemia and normoalbuminuric (0.8 L) and microalbuminuric (0.2 L) patients with type 1 diabetes. 33,34 Elevated shedding products, reflecting ESL breakdown, have been found in patients with severe sepsis, CKD, or ESRD, patients on dialysis, patients after major vascular surgery, and patients during acute or chronic hyperglycemia. 31,33,[35][36][37][38][39][40] Most of these conditions associated with a perturbed ESL are also characterized by an expanded ECV, higher BP, or both, suggesting that variability in sodium homeostasis and salt sensitivity may be related to the quality of the ESL, in which endothelial GAGs act as an intravascular buffer compartment for sodium.…”
Section: Esl Functionmentioning
confidence: 99%
“…[30][31][32] Great variability in systemic ESL volume has been reported between different medical conditions, regardless of how ESL volume was estimated. [33][34][35] Mean systemic ESL volume in healthy individuals was shown to be 1.5-1.7 L, whereas much lower systemic ESL volumes were found in treated (1.1 L) and untreated (0.8 L) patients with heterozygous familial hypercholesterolemia and normoalbuminuric (0.8 L) and microalbuminuric (0.2 L) patients with type 1 diabetes. 33,34 Elevated shedding products, reflecting ESL breakdown, have been found in patients with severe sepsis, CKD, or ESRD, patients on dialysis, patients after major vascular surgery, and patients during acute or chronic hyperglycemia.…”
mentioning
confidence: 99%
“…Rosuvastatin can partially restore glycocalyx volume in familial hypercholesterolaemia. However, it is uncertain whether this was a direct statin effect, or related to the improved lipid status [42].…”
Section: Damage To the Endothelial Surface Layermentioning
confidence: 99%